Communication surrounding initiation and withdrawal of non-invasive ventilation in adults with Motor Neuron(e) Disease: clinicians' and family members' perspectives. (September 2021) - Chapman, Charlotte; Bayes, Sara; Sim, Moira
Introduction: International guidelines recommend that health care clinicians communicate with people with MND and their family members about non-invasive ventilation (NIV) and percutaneous gastrostomy tube (PEG) prior to or at the onset of respiratory symptoms. This study sought to discover the degree to which these recommendations are followed in practice. Methods: Interpretive Description methodology was employed. Nineteen clinicians experienced in caring for people with MND, six relatives of recently deceased people with MND and one person with MND participated in semi-structured in-depth interviews. Clinicians' accounts of NIV and PEG related communications were compared to family member participants' recollections of their own discussions with clinicians. Data were analysed thematically. Results: Six major themes emerged that together capture the factors that impact practitioner-patient-family communications about NIV and PEG. Some clinicians were unaware of MND guidelines particularly communicating the burdens or possible withdrawal of NIV or found them challenging to implement. Consequently, family participants reported that they and their relatives with MND found clinicians' communication on these topics inadequate. This led to them 'topping up' their knowledge from less authoritative sources, predominantly the internet. Discussion: Clinicians' lack of awareness of the international guidelines and discomfort about discussing the benefits and burdens of NIV and PEGs means some people with MND and their families may be unprepared for the consequences of using and ceasing NIV.